Do Great Minds Prefer Alike? Thirteen-Month-Old Infants Generalize Personal Preferences Across Objects of Like Kind but Not Across People - Liu, Siying; Sun, Renji (Frontiers in Psychology, 2018)
Human preferences are person-specific because different individuals do not necessarily have the same preference. Although existing empirical evidence demonstrates that infants have a basic understanding about people’s preferences, there remained one question as to whether infants appreciate that a person’s preference can be generalized to objects that belong to the same kind. This study addressed this gap with 13-month-old Chinese infants. In Experiment 1, infants were first habituated to an actor preferring a target object over a different shaped distractor object. Next, the objects’ position and colors were changed and infants watched the actor from habituation and a new actor each alternated preference between the two objects. Results revealed that infants looked longer at the event when the old actor preferred the distractor object. Throughout the experiment, infants were also presented with additional tests in which each actor requested them to visually identify his or her preferred object. Results showed that infants identified the different colored target object for the old actor but not for the new actor. Experiment 2 removed the additional tests and replicated the results of Experiment 1. Experiment 3 confirmed that 13-month-olds could differentiate the two different colored target objects. Together, the present findings provide the first known evidence that 13-month-old expect object preferences to be generalized across objects of like kind but not necessarily across individuals. Such sensitivity to the rules guiding preference generalization could help infants predict people’ behaviors and facilitate more successful social interactions.